L’orientation comme recherche du meilleur compromis entre les inclinations personelles et les exigences des professions - Draime, Jacques; Walgraffe, Ria (Canadian Journal of Counselling and Psychotherapy, 2011)
Counsellors provoke in those who consult them a procedure of self-clarification. To attain the expected results of this procedure implies research in two areas: 1) knowledge of self, and 2) knowledge of the profession. The theoretical concept underlying the practice at the "Centre d'orientation et de consultation psychologique et pédagogique" at the Université catholique de Louvain is based on theories and research by Leopold Szondi and Martin Achtnich. From the point of view of the psychological structure of professional interests, each person disposes of a luggage made up of eight basic elements called inclinations. The "Berufsbildertest" is a photographic, projective test of the professions and is meant to clarify one's professional inclinations. It is through the actualization of the similarities between the individual inclinations structure and the professional requirements structure that an individual will be able to develop harmoniously in his or her professional life.